Physicochemical and functional characteristics of peach cv. Esmeralda fertilized with different doses of nitrogen - Navroski, Renan; Barreto, Caroline Farias; Cantillano, Rufino Fernando Flores; Vizzotto, Márcia; Nava, Gilberto (Comunicata Scientiae, 2023)
The aim of this study was to evaluate the physicochemical and functional characteristics of fruits yielded by peach trees which were fertilized with different doses of nitrogen. The experiment, which was installed in 2014. It had a randomized complete block design with four replicates. The nitrogen rates applied were 0, 40, 80, 120, and 160 kg N per hectare. Fruits were harvested in four crops in a row (2014, 2015, 2016, and 2017). The parameters were evaluated: soluble solids, pH, titratable acidity, epidermis and pulp firmness, attributes of pulp color, carotenoids, phenolic compounds, and antioxidant activity. Responses were only related to luminosity in the first crop. However, N fertilization influenced not only the soluble solid content, pH and chroma in the second crop but also all attributes of color in the third crop. SS, pH, ºHue and chroma differed among treatments in the fourth crop. The more N in the first three crops, the more carotenoids. Phenolic compounds decreased significantly in the 2016 crop whereas antioxidant activity diminished in both the 2015 and 2016 crops. Even though an ideal dose of N cannot be recommended due to high variation in attributes in the years under evaluation, it is needed because of other factors, such as weat her.